Group 14 element-based non-centrosymmetric quantum spin Hall insulators with large bulk gap - Ma, Yandong; Kou, Liangzhi; Du, Aijun; Heine, Thomas (Nano Research, 2015)
To date, a number of two-dimensional (2D) topological insulators (TIs) have been realized in Group 14 elemental honeycomb lattices, but all are inversionsymmetric. Here, based on first-principles calculations, we predict a new family of 2D inversion-asymmetric TIs with sizeable bulk gaps from 105 meV to 284 meV, in X2–GeSn (X = H, F, Cl, Br, I) monolayers, making them in principle suitable for room-temperature applications. The nontrivial topological characteristics of inverted band orders are identified in pristine X2–GeSn with X = (F, Cl, Br, I), whereas H2–GeSn undergoes a nontrivial band inversion at 8% lattice expansion. Topologically protected edge states are identified in X2–GeSn with X = (F, Cl, Br, I), as well as in strained H2–GeSn. More importantly, the edges of these systems, which exhibit single-Dirac-cone characteristics located exactly in the middle of their bulk band gaps, are ideal for dissipationless transport. Thus, Group 14 elemental honeycomb lattices provide a fascinating playground for the manipulation of quantum states. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2023-03-20
Keywords: band inversion; Dirac states; Group 14 honeycomb lattice; strain engineering; topological insulators; two-dimensional crystal